(3GdfXGe GdbGfhfj dGfOeGL GdTQcGJ (B/s - (3GdUZjQ, MSGe GdOjf YHO GdZfjs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdacQ GdLGeYj,s, 2016)
(3jJfGhd cJGH (B((3GdfXGe GdbGfhfj dGfOeGL GdTQcGJ(B) (3hGdPj bGe HJCdjag (B((3MSGe GdOjf YHO GdZfj GdUZjQ(B) (3aj MhGdj (B(670) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GfOeGL GdTQcGJ(B-(3GdTQcGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdJegjOj (B: (3Gdeaghe GdbGfhfj ddGfOeGL, GdHGH GdChd (B: (3eTQhY GdGfOeGL, GdHGH GdKGfj (B: (3bhGYO hELQGAGJ GdGfOeGL, GdHGH GdKGdK (B: (3BKGQ GdGfOeGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B632-633.s
Keywords: (3GfOeGL GdTQcGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdTQcGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs